Методичні особливості дослідження цифрової трансформації країн та регіонів світу. - Ємчук, Тетяна Володимирівна; Цепенда, Микола Михайлович (Географія та туризм: науковий журнал, 2025)
The purpose of the study is a theoretical and methodological justification of the process of assessing the digital transformation of society in countries and regions of the world, which includes the development and systematization of approaches to measuring the level of digitalization, determining key indicators and methods of geographical analysis. Methods. An analysis of scientific sources was carried out, including articles by domestic and foreign authors that highlight the issues of digital transformation, its theoretical and methodological foundations and geographical features. Using methods of comparison, generalization and system analysis, the main approaches to assessing the level of digital transformation were determined, and key indicators that characterize this process in different countries and regions of the world were identified. Results. Key approaches to assessing digital transformation were determined; methodological approaches to assessing the digital transformation of society were systematized, which allows to streamline the measurement process and identify key indicators of digitalization; systematized the main indicators of digital transformation, in particular the level of access to information and communication technologies (ICT), digital skills of the population, the Географія та туризм 33 prevalence of electronic services and the impact of digitalization on the economy; developed an assessment algorithm that includes defining goals, selecting criteria, collecting data, calculating indicators and analyzing results. Scientific novelty. The concept of digital transformation is clarified in the context of its geographical analysis, which allows assessing this process not only as a technological phenomenon, but also as a spatial pattern of social development. An algorithm for assessing digital transformation is proposed, which includes defining criteria, collecting data, processing and analyzing them, which can serve as the basis for further research and practical application. Practical significance. The results of the study can be used by government agencies, think tanks and researchers to monitor the level of digitalization in different countries and regions. The identified key indicators of digital transformation can serve as the basis for developing digital development strategies at the national and regional levels. The results of the study can be applied in the educational process to train specialists in the field of digital economy, geography and management.
Keywords: цифрова трансформація; цифровий розрив; інформаційно-комунікаційні технології; просторовий аналіз